The new method of identification of extremes groups based on epistatic interaction effect using molecular markers - BOCIANOWSKI, JAN (The Indian Journal of Agricultural Sciences, 2026)
Additive × additive epistatis interaction is an important and integral feature of the genetic architecture of quantitative traits. Epistasis is difficult to detect in classical quantitative analyses based on resemblance between relatives in outbred populations. In traditional quantitative genetics estimation of the additive × additive epistasis effect on the basis of phenotypic observations requires identification of the groups of extreme lines, i.e. group of minimal lines and group of maximal lines. Minimal and maximal lines contain, respectively, only alleles decreasing and only alleles increasing the value of the trait. Because the genotype has not been known, to extreme groups were usually put lines with minimal and maximal expression of the observed traits. Estimates obtained by this way are biased. Therefore, in this paper estimation of the parameter connected with the additive × additive epistasis genes interaction effect on the basis of extreme groups of doubled haploid lines identified on the basis of molecular marker data is presented. Numerical analysis was made on the basis of three populations of doubled haploid lines of barley (Hordeum vulgare L.), viz. 120 DH lines from the Clipper × Sahara 3771 cross, 145 DH lines from the Harrington × TR306 cross and 150 DH lines from the Steptoe ´ Morex cross. In total, 157 sets of observations were analyzed. The estimates of additive × additive epistasis effects from proposed (extreme lines) method are much less biased than the estimates obtained by quantile method.